Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PDAM Kota Tomohon - Worang, Angela; Runtuwene, Roy F. (Sam Ratulangi University, 2019)
This research was conducted in PDAM Tomohon City which has the purpose of this study to: 1) knowing the effect of motivation on the performance of PDAM Tomohon City employees; 2) knowing the influence of work discipline on the performance of PDAM Tomohon City employees; 3) knowing the motivation and work discipline on the performance of PDAM Tomohon City employees. Where employees are required to have knowledge and skills must also have experience of motivation and discipline as well as performance, but basically PDAM Tomohon City employees ignore motivation and discipline as well as existing performance. This type of research is a type of associative and quantitative descriptive research. The sample used was 60 employees. Data collection techniques used in this study used questionnaire and library methods. To examine the influence of motivation and discipline on performance by using multiple linear regression test analysis techniques. The tools used in testing data instruments are validity and reliability tests; classic assumption test (normality test, multicellularity test, and heteroscedasticity test). The results of this study show that motivation variables and work discipline simultaneously influence the performance of PDAM Tomohon city employees, while partially motivation has a significant effect on performance, and discipline does not affect the employee performance of PDAM Tomohon City.